Structural characterization and immunomodulatory activity of Grifola frondosa polysaccharide via toll-like receptor 4–mitogen-activated protein kinases–nuclear factor κB pathways. Issue 6 (25th May 2016) - Ma, Xiaolei; Meng, Meng; Han, Lirong; Cheng, Dai; Cao, Xiaohong; Wang, Chunling
Abstract : We isolated a neutral polysaccharide from the fruiting body of a mushroom Grifola frondosa (GFP-A). Abstract : We isolated a neutral polysaccharide from the fruiting body of a mushroom Grifola frondosa (GFP-A). The aim of this study was to characterize a neutral α-d -polysaccharide derived from G. frondosa and evaluate its immunomodulatory effect on toll-like receptor 4, mitogen-activated protein kinases and nuclear factor κB pathways of protein expression in macrophages. The structural features of GFP-A were characterized by physicochemical and instrumental analyses. Its molecular weight was found to be 8.48 × 10 2 kDa. The main chain of GFP-A consisted of (1 → 4)-linked and (1 → 6)-linked α-d -glucopyranosyl, and (1 → 3, 6)-linked α-d -mannopyranosyl residues, which branched at C-3. The branches consisted of (1 → 6)-linked α-d -galactopyranosyl and t-l -rhamnopyranosyl residues. An in vitro immunomodulatory assay for pro-inflammatory cytokines (interleukin-1β, interleukin-2, tumor necrosis factor alpha, etc. ) using the macrophage cell line, RAW 264.7, revealed that GFP-A exhibited significant immunomodulatory activity by stimulating the toll-like receptor 4, mitogen-activated protein kinases to nuclear factor κB/pathway.